2017
DOI: 10.3389/fmicb.2017.01738
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm Activities from Bergenia crassifolia Leaves against Streptococcus mutans

Abstract: Streptococcus mutans has been reported as a primary cariogenic pathogen associated with dental caries. The bacteria can produce glucosyltransferases (Gtfs) to synthesize extracellular polysaccharides (EPSs) that are known as virulence factors for adherence and formation of biofilms. Therefore, an ideal inhibitor for dental caries is one that can inhibit planktonic bacteria growth and prevent biofilm formation. Bergenia crassifolia (L.), widely used as a folk medicine and tea beverage, has been reported to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 44 publications
(44 reference statements)
1
42
0
Order By: Relevance
“…Other natural products or components such as polyphenolic extract from Rosa rugose tea, methanolic fraction of Zingiber officinale or kinds of leaves extract, were also demonstrated to display inhibitory effect on QS and biofilm development [53][54][55]. It was reported that ethanol extract from Rhodomyrtus tomentosa (Aiton) Hassk.…”
Section: Othersmentioning
confidence: 99%
“…Other natural products or components such as polyphenolic extract from Rosa rugose tea, methanolic fraction of Zingiber officinale or kinds of leaves extract, were also demonstrated to display inhibitory effect on QS and biofilm development [53][54][55]. It was reported that ethanol extract from Rhodomyrtus tomentosa (Aiton) Hassk.…”
Section: Othersmentioning
confidence: 99%
“…The results showed that with the increase of drug concentration, the thickness of bacterial biofilm gradually decreased; there is a concentration‐dependent effect between thickness and concentration (Table 3). The formation of bacterial biofilm is a three‐step dynamic process, followed by adhesion, aggregation, and maturity; the first step of adhesion is crucial to the formation of biofilm, which determines the subsequent development and maturity of biofilm (Liu et al, 2017). Our research shows that the T. chinensis Bunge can inhibit the growth of S. mutans and the formation of its biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Minimum bactericidal concentrations (MBCs) were determined by plating the bacterial suspensions from the MIC assay wells at the peptide concentrations equal to or higher than the MIC values on solid agars. The lowest peptide concentrations at which there was no bacterial growth on plates after incubation were taken as the MBC (Liu et al, 2017). Resazurin microtiter assay was also performed as previously described to determine the MIC (Palomino et al, 2002).…”
Section: Determination Of the Minimum Inhibitory Concentration And MImentioning
confidence: 99%
“…Human oral epithelial cells (HOECs) were purchased from Shrdio Company (Nanjing, China). The cytotoxicity of GHc or GHd on HOECs was evaluated by a Cell Counting Kit-8 (CCK-8) assay (Beyotime Biotechnology, China) (Alaufi et al, 2017;Liu et al, 2017). HOECs were grown in Dulbecco's modified Eagle's medium (DMEM) containing 10% fatal bovine serum (FBS) and cultured in a humidified atmosphere of 5% CO 2 at 37°C.…”
Section: Cytotoxicity Of Ghc or Ghd On Human Oral Cellsmentioning
confidence: 99%